Movimento negro e as políticas de promoção da igualdade racial no Espírito Santo - Cruz, Suellen Silva da (2019)
The present study is the result of reflections on the participation of the Negro Movement of Espírito Santo in the process of implementing policies to promote racial equality in Espírito Santo. The central theme is the construction and implementation of important laws, regulations and actions carried out throughout history as a form of government response - federal and state - to the tension made by the Black Movement. In this context, through successive problematizations about the limits of social policies in contemporary capitalism, the purpose of this dissertation is to analyze the participation of the Black Movement in the process of implementing policies to promote racial equality in the state of Espírito Santo. To see how this participation brought impacts on the effectiveness of the policy in the period from 2003 to 2016 was an issue that permeated the entire study. Methodologically we try to answer this question through the incorporation of two categories that we consider fundamental for the analysis made in this research: totality and historicity. For that, an extensive bibliographical review was necessary to find out about the existing productions on the proposed study topic, in addition to documentary research - legislation, final report of the III Conference and data collected in the Official Gazette of the State of Espírito Santo. The qualitative approach of the research and we use widely the bibliographical research of authors who work the history of the black movement in soil capixaba. In addition, as a technique for collecting data and information in the field we used the interview. As a result, we have been able to conclude that since the confrontations and struggles of the pre-abolition period, all progress in history on minimum policies of protection and reparation for the black people has been won only on the basis of much collective organization and articulated resistance.